Global health and orthopaedic surgery—A call for international morbidity and mortality conferences. (2015) - Sheth, Neil P.; Donegan, Derek J.; Foran, Jared R.H.; Sugarman, Jeremy
Highlights: There is a large discrepancy between the supply and demand of surgical services in the developing world, especially for nations in Sub-Saharan Africa. There has been longstanding and growing interest from the developed world in assisting the developing world, including providing surgical services. This case demonstrates the ethical challenges that can be created from performing surgical procedures in the developing world without concomitant access to appropriate patient follow-up or resources for treating post-operative complications. Consequently, there is a need for a new paradigm which provides a more sustainable solution with increased local capacity to treat complications associated with surgical procedures. Until adequate infrastructure is developed, the informed consent process for surgery in this setting should include a frank discussion about not only potential surgical complications, but also the possibility that they may not be able to be managed appropriately given constrained local resources. In the interim, a forum such as a written morbidity and mortality conference can help provide rich descriptions of the issues and problems that are encountered so as to increase awareness of them so that appropriate solutions can be identified. Abstract: Introduction: There is a large discrepancy between supply and demand of surgical services in developing countries. This inequality holds true in orthopaedic surgery and the delivery of musculoskeletal care. Intertwined amongst the decision to perform surgical procedures in the developing world are the ethics of doing so – just because one is capable of performing a procedure, should it be done? Presentation of case: A 31 year-old female with end-stage joint destruction underwent a left total hip replacement by a foreign orthopaedic team in Tanzania. She had a favorable outcome for 8 months, but is now diagnosed with tuberculosis and a deep space infection in her prosthetic left hip – an unsolvable problem in the developing world. Discussion: This case demonstrates the ethical challenges that can be created from performing surgical procedures in the developing world without concomitant access to appropriate patient follow-up or resources for treating post-operative complications. While the current system is inadequate to manage the burden of disease, these inadequacies may be exacerbated at times by post-operative complications resulting from well-intentioned surgical missions. Conclusion: This case illustrates many difficulties in caring for individuals in the developing world, raising several questions: (1) How can complications be prevented in the future? (2) What are possible ways of managing complications with resources at hand once it occurs? (3) What resources are needed to minimize patient? Ideally an international forum can help provide descriptions of issues and problems that are encountered so as to increase awareness and identify potential solutions.